"To Restore the Soul of America": How Domestic Anti-Racism Might Fuel Global Anti-Racism. (22nd January 2021) - Lovelace, H. Timothy
Abstract : On November 7, 2020, President Joe Biden proclaimed that his administration would "restore the soul of America." He declared that U.S. voters had given him a mandate "to achieve racial justice and root out systemic racism in this country, " and that he plans to use the nation's restored moral leadership to create international consensus around U.S. values and urge foreign nations and intergovernmental institutions to adopt anti-racist agendas. To be sure, Biden's commitment to ending systemic racism is rooted in troubling notions of U.S. exceptionalism and invokes an unfounded anti-racist nostalgia. We should never "restore" America's racial past. Nevertheless, Biden's commitment is, in many ways, refreshing and raises a crucial and productive question: how might the United States recalibrate the international legal order and address systemic racism within Biden's framework? One straightforward and pragmatic answer emerges: the Biden administration should live up to the standards of those who inspired his campaign's mission. In other words, truly improving the racial order at home might be a viable way to advance anti-racism abroad, including through existing international institutions.